Impact of head-down-tilt body position on abdomen resistance for urinary bladder monitory applications - Freeborn, Todd J.; Critcher, Shelby; Hooper, Gwendolyn L. (Frontiers in Electronics, 2024)
Tissue electrical impedance (or bioimpedance) is a quantity related to the passive, frequencydependent electrical properties of a biological tissue and is a promising modality for continuous monitoring of relative bladder volume and bladder activity. In this study, the impact of body position (specifically 6 • head-down-tilt) intended to induce fluid redistribution and therefore result in a change in the electrical resistance of the abdomen is evaluated. The abdomen resistance (10 kHz to 100 kHz) of 9 healthy young adults was measured before and after 240 minutes in 6 • head-down-tilt. Over this period, the resistance increase was not statistically significant even though the average bladder volume increased 506 mL. It was expected that the abdomen resistance would decrease with increasing bladder volume over this period. The masking of the expected resistance decrease is attributed to the shift in fluid from legs/abdomen to neck/chest caused by the head-down-tilt body position over this period. Overall, this suggests that methods to differentiate bladder volume changes from other types of fluid shifts in the body are needed for resistance based monitoring in free-living conditions.